Istotne naruszenie zobowiązania jako przesłanka odpowiedzialności kontraktowej w Konwencji Wiedeńskiej - Napierała, Jacek (Wydział Prawa i Administracji UAM, 1994)
The use of a uniform institution of a "breach of contract" does not rule out the practicability of combining specific sanctions with certain types of breach. In this respect a fundamental breach plays an important role in the Vienna Convention. The article aims at systemizing the problems arising in the practical application of this institution. A fundamental breach is singled out on its basis of its result, namely: (1) the loss of either party's interest; (2) which was unpredictable. The combination of certain sanctions with a qualified form of an infringement to the creditor's interest gives rise to the question about the criterion of such qualification. Four criteria were considered during discussions about the uniform law for contracts of sale. The Convention decided in favour of the degree of dissatisfaction of the creditor's expectations related to performance as the criterion of a "fundamental" breach. The degree of dissatisfaction depends for instance on the possibility of removing a defect from delivered goods. The last opinion can be proven by describing the fundamental nature of breach without making reference to provisions relating to sanctions in case of such breach. Institutions of Polish law having their counterparts in the Convention are presented in the conclusion.
A fundamental breach of contract as a premise of contractual liability under the Vienna Convention